Kekuatan Alat Bukti Keterangan Saksi yang Memiliki Hubungan Darah dengan Terdakwa dalam Tindak Pidana Pencurian dalam Keluarga - I Gede Agus Sudiantara; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2021)
The strength of evidence from witnesses who have family ties to the defendant in the crime of theft in the family, the process of examining witnesses is the main evidence in a crime. The purpose of this study is to reveal the strength of the evidence of witnesses who have blood relations with the defendant in the evidentiary process and barriers to proof by using evidence of witnesses who have blood relations with the defendant in the crime of theft in the family. The research method used is normative legal research. Sources of primary and secondary legal materials. Legal materials that have been obtained from the literature study and the approach to legislation were analyzed using a systematic interpretation technique. The results of the study reveal that witness testimony is very necessary in the trial in order to provide appropriate sanctions for the defendant. The barrier to proof from witness statements who have family relationships and ties is if the minimum principle of proof cannot be proven. It can be concluded that the strength of the testimony of a witness who does not take an oath, cannot be considered as evidence, but only information that is considered by the judge.